Fuel Dynamics Following Wildfire in US Northern Rockies Forests - Stevens-Rumann, Camille S.; Hudak, Andrew T.; Morgan, Penelope; Arnold, Alex; Strand, Eva K. (Frontiers in Forests and Global Change, 2020)
Accumulation of dead woody material is a critical management concern following wildfires, especially given the possibility of subsequent wildfires. Forest structure and fuel accumulation are largely driven by site climatic conditions, so variability in site conditions is important to consider in management beyond the one-size fits all model for post-fire fuel dynamics. Moreover, dead woody material provides important ecological functions for forested ecosystems. Understanding when surface fuels biomass is highest following wildfires and how these dynamics change after repeated fires affords land management agencies opportunities to adjust fuel reduction strategies without removing large quantities of dead trees that are important in these post-fire landscapes for a variety of ecosystem services, including wildlife, water and nutrient retention, and soil stabilization. Here we examined how surface fuels and standing dead trees change over time, by burn severity, site climate, and with repeated fires at seven different years-since-fire (1-24 years) across 182 sites from ten wildfires in central Idaho. Downed woody fuel loads were higher on moister and cooler sites. Large-diameter woody fuels saw significant increases after about 14 years post-fire while smaller woody fuels had the highest loads at 20 years post-fire. Surface fuel loads varied by burn severity and years since fires, with the highest loadings at longer years since fire and sites burned in stand replacing fire. Litter and duff had not sufficiently accumulated to compensate for continued decomposition, resulting in lower forest floor biomass through 24 years post fire. Density of snags of all sizes generally declined after 7-9 years, but large-diameter snags were still standing 24 years post fire. Repeated fires resulted in >40% reduction in both surface fuels and standing trees compared to once-burned areas at the same years since fire. Burned landscapes can serve a great ecological benefit by providing an infusion of both standing and downed dead woody debris. Additionally, though some sites burned in stand replacing fires exceed recommended surface fuel loadings, these ecological considerations should be weighed against concerns about reburning potential and fire fighter hazards.